#### Answer

$13$

#### Work Step by Step

$\sqrt {-13}\sqrt {-13} = \sqrt {-13 \times-13} = \sqrt {169} = 13$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$13$

$\sqrt {-13}\sqrt {-13} = \sqrt {-13 \times-13} = \sqrt {169} = 13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.